Is the “One Province One Rate” premium policy reasonable for Chinese crop insurance? The case in Jilin Province - Xian-hua ZHOU; Pu LIAO; Ke WANG (Journal of Integrative Agriculture, 2018)
Crop insurance in China is currently adopting the premium pricing strategy of “One Province One Rate”, which appears to be in line with the systematic risk characteristics within crop insurance. This research aims to investigate the theoretical rationalization of this pricing strategy and its implications using the spatial lag model and the county-level data from the 45 corn plant counties of Jilin Province, China. Results corroborate that: (1) the spatial spillover effect of the corn yield risk is significant in Jilin but decreases rapidly when the risk unit includes more than eight counties; and (2) separating Jilin Province into eight risk zones for corn insurance will significantly reduce the high cross-subsidy phenomenon arising from the “One Province One Rate” strategy and shall benefit poor peasants in the region as well. This paper not only proves the existence of a systematic risk of crop insurance but also reveals that the spatial correlation and systemic features of the crop yield risk do not create a solid foundation for the current pricing strategy of “One Province One Rate”. These conclusions will undoubtedly provide important references and empirical evidence for the role of China's crop insurance in poverty alleviation.